Spotted Wing Drosophila Drosophila suzukii (Matsumura) (Insecta: Diptera: Drosophilidae) - Rajinder S. Mann; Lukasz L. Stelinski (EDIS)
Most Drosophila flies are associated with rotten or over-ripened fruits and are nuisance pests. However, a few species such as the spotted wing drosophila, D. suzukii (Matsumura), can infest un-ripened fruits and are of economic significance. First detected within the continental United States in August 2008, D. suzukii has become a serious threat to fruit crops. This 6-page fact sheet was written by Rajinder S. Mann and Lukasz L. Stelinski and published by the UF Department of Entomology and Nematology, May 2011.